THE HISTORY OF PILGRIMAGE TOURISM AND ITS ROLE IN THE FIELD OF TOURISM (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Pilgrimage tourism is currently a widespread tourism industry. Pilgrimage tourism is essentially the process of visiting places of pilgrimage. Pilgrimages are usually long journeys of days, weeks or even months for religious purposes. In this article, we will dwell on the description of pilgrimage tourism, its essence, and how important it is today.